TRANSIENT SIMULATION OF IMPULSE WIND EFFECT ON A TALL SHIPYARD FRAME STRUCTURE - Radoicic, Goran Nikola; Jovanovic, Miomir Ljubomir (Journal of Applied Engineering Science, 2017)
This paper presents the importance of a dynamically checked design of the shipbuilding portal rotating crane geometry regarding wind load. The gust of wind is modelled as a wave quantity variable in time and altitude of flow. The research is performed by non-linear transient FEM analysis. Structural damping is modelled by conversion to the equivalent viscous damping. Eigenfrequencies are obtained by applying the Lanczos method. The paper contains an originally developed dynamic model and experimentally verified stiffness of the structure. Through several case studies, the paper indicates a greater danger of a multi-wave wind gust at the steady state of wind speeds statistically recorded in relation to a single-wave wind gust at the extremely recorded speed. Based on the conducted dynamic simulations of wind action a new design criterion is suggested – the conditional quotient of structural geometry.